MARCHING FORWARD AS SOLDIERS OF CHRIST? THE CONTRIBUTIONS OF THE EVANGELICAL LUTHERAN CHURCH TO THE RECONSTRUCTION OF ZIMBABWE, 2000-2013 - Maposa, Richard S. (Scriptura, 2014)
World-over, the contributions of churches to transforming societies cannot be overstated. Nevertheless, today the churches in Zimbabwe are standing at a crossroad, in search of relevance and identity in the eyes of the majority of the ordinary people who are experiencing poverty and injustice. There have been many events in the political history of the country, beginning from the year of the controversial land reform programme in 2000. Over the past decade every facet of life has been markedly affected by its paradoxical effects. The detrimental effects have been responsible for bringing about the much-acclaimed ‘Zimbabwe crisis’, and causing grinding poverty for the majority of citizens. Accordingly, the purpose of the study is to examine some Christian responses to this phenomenal crisis. Given the diversity of the Christian churches in Zimbabwe, the earliest responses were watchfully cautious. This lukewarm attitude was largely dictated by the fear of inviting unspecified reprisals from the machinery of the State. Nevertheless, as the myriad of crises continued to mount, the churches reconsidered their divine mandate and decided to march forward as ‘Soldiers of Christ’ in order to take the bull by its horns. Specifically, this article focuses on the contributions of the Evangelical Lutheran Church in Zimbabwe (ELCZ) as it attempts to bring about a renaissance and the regeneration of sustainable development in Zimbabwe. Judging from the context of its activities to mitigate the socio-economic and political challenges facing the country, the ELCZ is being inspired by a liberationist paradigm of doing theology, whether in the broad fields of education, health, policy advocacy or pastoral ministry